Dynamics of Work from Home in The Time of Pandemic Covid-19 as The Implementation of The Industrial Revolution 4.0 - Akmal Maulidina; Zainur Hidayah; Anita Maharani (Universitas Trisakti, 2021)
The Industrial Revolution 4.0, which is echoing in Indonesia, will be proven during the Covid-19 pandemic viewed from the economic and social aspects through the application of work from home (WFH). Purpose: This study aims to analyze the implementation of the 4.0 industrial revolution through work from home during the Covid-19 pandemic on employee performance. Research methodology: determining to sample for research with purposive sampling technique as in total received 104 data. The collected research data is still acceptable because the rate-of-returned questionnaire is> 80%. The research hypothesis testing carries out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Results: From the results of the analysis carried out, found that only the first hypothesis, namely the use of information technology, was proven to have a significant effect on commitment, while the rest proved to be. Limitations: This study has restrictions to aspects tested referring to the respondents' perceptions. Contribution: The contribution of this research is in the area of human resource management, especially in terms of commitment, use of information technology, work-family conflict and performance.